Effect of age on the reproductive fitness of Platygaster demades an egg parasitoid of apple leafcurling midge - Sandanayaka, W.R.M.; Chhagan, A. (New Zealand Plant Protection, 2008)
Platygaster demades is an egg parasitoid of the apple leafcurling midge (ALCM) Dasineura mali Each P demades female carries a mean preovipositional load of 1380 263 eggs Females fed with buckwheat nectar lived a maximum of 10 weeks at 15C The agedependent reproduction of female P demades was determined by a laboratory experiment at room temperature ALCM eggs on apple shoots were exposed to 1 2 4 8 and 10weekold individual P demades females and ALCM larvae that emerged from the parasitised eggs were reared on fresh apple shoots and allowed to pupate on a layer of moist soil The numbers and sex of adult P demades that emerged from the ALCM pupae were recorded Older females (8 and 10 weeks old) were able to locate and parasitise host eggs and produced as many offspring as younger females The implication of the results in terms of the reproductive fitness of P demades is discussed